Processing of Ginger Rhizomes and Moringa Leaves as an Effort to Maintain Body Health in the Village of Tarik Sidoarjo: Pengolahan rimpang jahe dan daun kelor sebagai Upaya Menjaga Kesehatan Tubuh Di Desa Tarik Sidoarjo - Arista Wahyu Ningsih; Ivan Charles S. Klau; Yani Ambari; Dewi Rahmawati; Bella Fevi Aristia; Khurin In Wahyuni (Yayasan Ahmar Cendekia Indonesia, 2023)
Indonesia is also affected by the coronavirus or Covid-19. Not only multivitamins but these spices are also consumed by residents. Low public knowledge related to the use of herbal medicines can result in not helping to maintain the body's immune system in preventing Covid-19. From this background, Training and Assistance in Making Immune System Enhancement Products to Preventing Infections are needed. The community service stage in Tarik Village is carried out face-to-face by fulfilling strict health protocols with the bureaucratic stages of applying for permits to village officials, preparing consumables for counseling and workshops on making herbal tea for ginger rhizomes and Moringa leaves, counseling and workshops on making herbal tea for ginger rhizomes and Moringa leaves, assistance in making herbal tea for ginger rhizomes and Moringa leaves and evaluating the implementation of community service. From the results of the training and mentoring carried out, there was an increase in knowledge which was initially 21% to 68%, there was a decrease from the fair-know category which was originally 49% to 43% and a decrease in the less know category from 81% to 11%. The herbal tea training received enthusiasm from the participants and assistance in making herbal tea products to increase the immune system in preventing infections went smoothly and was characterized by an increase in the understanding of participants. Abstrak Indonesia juga terdampak dengan virus corona atau Covid-19. Tidak hanya multivitamin tetapi rempah-rempahan ini juga dikonsumsi oleh warga. Pengetahuan masyarakat yang rendah terkait dengan penggunaan obat herbal dapat berakibat tidak membantu menjaga sistem imun tubuh dalam preventif Covid-19. Dari latar belakang tersebut maka Pelatihan Dan Pendampingan Pembuatan Produk Peningkatan Sistem Imun dalam Mencegah Infeksi sangat dibutuhkan. Tahapan pengabdian masyarakat di Desa Tarik dilaksanakan secara tatap muka dengan memenuhi protokol Kesehatan ketat dengan tahapan birokrasi permohonan izin kepada perangkat desa, penyiapan bahan habis pakai untuk penyuluhan dan workshop pembuatan teh herbal rimpang jahe dan daun kelor, penyuluhan dan workshop pembuatan teh herbal rimpang jahe dan daun kelor, pendampingan pelatihan pembuatan teh herbal rimpang jahe dan daun kelor dan evaluasi pelaksanaan pengabdian masyarakat. Dari hasil pelatihan dan pendampingan yang dilaksanakan terdapat kenaikan pengetahuan yang awalnya 21% menjadi 68%, terdapat penurunan dari kategori cukup tahu yang awalnya 49% menjadi 43% dan penurunan kategori kurang tahu dari 81% menjadi 11%. Pelatihan teh herbal mendaptakan antusias dari peserta Dan Pendampingan Pembuatan Produk Teh Herbal Untuk Peningkat Sistem Imun Dalam Mencegah Infeksi berjalan dengan lancar dan ditandai dengan terjadi peningkatan pemahaman peserta.